Perancangan Simulasi Pembelajaran Kriptografi Klasik Menggunakan Metode Web Based Learning - Jefril Rahmadoni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
One of the main problems in the education system in Indonesia is a quality problem and the results of the learning process. This problem relates to the provision of learning materials and materials that have not been widely accessible without being limited by the constraints of distance and time. In realizing this requires a change in the paradigm of the learning process has been applied so far as implementing e-learning. To achieve these objectives developed model of e-learning by using web- based learning. Web based learning (WBL) is the learning associated with the teaching materials are presented via a web browser. Web-based learning applications created using programming languages PHP and MySQL. The results of a web-based learning can facilitate students in the learning process and provide information services in understanding a material that has been displayed on web- based learning site Keywords : E-learning, Web Based Learning, Classic Cryptography